2012
DOI: 10.17925/enr.2012.07.01.46
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of the Multiple Sclerosis Nurse - Implications of Future Management Directions

Abstract: The role of the multiple sclerosis (MS) nurse is constantly evolving, owing to the introduction of new MS therapies and new patient treatment KeywordsMultiple sclerosis (MS) specialist nurse, MS nurse role, patient communication, MS nurse-patient relationships, MS therapies Disclosure: Chrysa Chrysovitsanou has no conflicts of interest to declare. Del Thomas has received honoraria and consultation fees from Merck Serono, Teva and Novartis.Martin Duddy has received honoraria for lectures and consultancy, expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…3 However, Wong et al reported that 50% of MS patients discontinue treatment with DMT within 2 years of initiation. 4 Given this high-reported patient "drop-out" and the importance of adherence to treatment, it behoves neurologists and nurses, due to their active role in MS treatment management and patient education, 5 to understand what contributes to adherence in order to design supportive interventions. Of particular importance is to understand practising clinicians' challenges with respect to their role in impacting adherence.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, Wong et al reported that 50% of MS patients discontinue treatment with DMT within 2 years of initiation. 4 Given this high-reported patient "drop-out" and the importance of adherence to treatment, it behoves neurologists and nurses, due to their active role in MS treatment management and patient education, 5 to understand what contributes to adherence in order to design supportive interventions. Of particular importance is to understand practising clinicians' challenges with respect to their role in impacting adherence.…”
Section: Introductionmentioning
confidence: 99%